Second language spoken fluency in monologue and dialogue - Kirk, Steven J. (2016)
Although second language spoken fluency has long been recognized as a major component of language proficiency, it has never been clearly defined. It has been shown that fluency is a complex phenomenon, with a host of relevant factors, and it has been suggested that it might be better separated into multiple concepts, such as cognitive fluency and utterance fluency. There is also evidence that fluency has a dialogic aspect, that is, that the fluency of a conversation is a co-construction of the two speakers, rather than simply alternating monologues. This can be observed in the confluence created by smooth turn exchanges, which results in minimizing gaps and avoiding overlap. The present study seeks to examine the co-construction of dialogic fluency through a parallel case study of two Japanese learners of English. One learner was of lower-intermediate proficiency, and the other was of higher proficiency, but both were able to create good impressions of fluency in conversations with native speakers of English. The case study design was semi-experimental in that it involved a story-retelling task done in monologue and dialogue, which was repeated to take into account the effect of practice. The case study allowed the close examination of the construction of fluency in the story-retelling task moment-by-moment through the course of the retellings, taking into account all relevant factors. The semi-experimental, parallel case study design allowed the findings to be compared (1) between monologue (where the learner recorded herself telling the story alone) and dialogue (where the learner told the story to a native speaker interlocutor), and (2) between the two learners of differing proficiency. This study was also mixed-methods in that it combined a qualitative, grounded theory approach to data analysis involving discourse analytic techniques, with quantitative comparisons of temporal variables of fluency. It was also multi-modal in that video was employed to take into account gaze, gesture, and head nods. Results of quantitative analyses revealed that the dialogues were comparatively more fluent than the monologues in terms of speech rate, articulation rate, and length of silences, for both speakers, although the higher-proficiency subject had faster speech and articulation rates than the lower-proficiency learner. This implies that narrative in dialogue is not just a listener occasionally backchanneling while the speaker delivers a monologue. The qualitative analyses revealed that the co-construction of smooth conversation was facilitated by the alignment of rhythm between the speaker and listener, supported by gaze, gestures, and head nods. The learners in these case studies were able to employ different fluency techniques for stressing words in phrases to create rhythm in spite of lower speech rates, and were able to adjust those techniques to maintain rhythm with even lower speech rates at difficult points of the story. These results confirm previous research that some apparent “dysfluencies” in speech should be considered as speech management phenomena, that positively contribute to the co-construction of fluent conversation. They also suggest that alignment between the speakers in terms of rhythm of speech and gaze are important in conversation, confirming previous research showing alignment at these and other levels of interaction. Finally, it appears that fluency is a multi-level construct, and that dialogic fluency should be considered a separate construct from cognitive fluency, of equal or more importance. This has implications for language testing, such that fluency may not be able to be captured with single test types, and for language teaching and learning more generally.